(untitled) (AYUSHDHARA, 2025)
According to an Indian systematic analysis, 34.4% of elderly individuals suffer from GD. Ayurveda considers aging (Jara) as a natural process associated with mental changes, including Vishada (depression), which is correlated with geriatric depression. Methods: A comparative analysis of contemporary medical perspectives and Ayurvedic principles was conducted to understand the etiology, pathophysiology, and treatment of geriatric depression. Literature from modern psychiatry and classical Ayurvedic texts was reviewed, emphasizing Vishada as a Vataja Nanatmaja Vyadhi and its correlation with GD. Evaluation methods included standardized depression scales like the Geriatric Depression Scale, PHQ-9, and Hamilton Depression Scale. Results: The study highlights key etiological factors of GD, including neurotransmitter imbalances, chronic illnesses, and psychosocial stressors in modern medicine, while Ayurveda attributes Vishada to vitiation of Vata and Tamas guna. Pathophysiology suggests depletion of Dhriti (mental strength), Smriti (memory), and Buddhi (intellect), leading to Vishada. Contemporary treatment primarily involves SSRIs, psychotherapy, and lifestyle interventions. Ayurveda recommends a whole system approach integrating Shodhana (purification), Shamana (pacification), Satvavajaya (mind therapy), Daivavyapashraya (spiritual healing), and lifestyle modifications. Conclusion: A multidisciplinary approach combining Ayurveda and modern medicine may offer a comprehensive strategy for GD management. Early diagnosis and integrative treatment can significantly improve the quality of life in elderly individuals.